2019
DOI: 10.1002/14651858.cd002850.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Telephone counselling for smoking cessation

Abstract: Background Telephone services can provide information and support for smokers. Counselling may be provided proactively or o ered reactively to callers to smoking cessation helplines. Objectives To evaluate the e ect of telephone support to help smokers quit, including proactive or reactive counselling, or the provision of other information to smokers calling a helpline. Search methods We searched the Cochrane Tobacco Addiction Group Specialised Register, clinicaltrials.gov, and the ICTRP for studies of telepho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 421 publications
7
173
0
7
Order By: Relevance
“…61,[189][190][191][192] Several Cochrane reviews have supported the effectiveness of these options and have showed enhanced behavioural support focusing on adherence to smoking cessation medications can improve adherence, and therefore recommends that interventions to increase adherence should address the practicalities and perception changes about taking medication. [191][192][193][194][195] As such, counselling interventions given outside routine clinical care by smoking cessation counsellors, including health educators and psychologists, could assist smokers to quit. 195 In respect to unwillingness to quit, in the UK about 40% of smokers do not want to quit, and despite the reduction in smoking rates across Europe since 2000, these rates are less pronounced compared to Australia and North America.…”
Section: Discussionmentioning
confidence: 99%
“…61,[189][190][191][192] Several Cochrane reviews have supported the effectiveness of these options and have showed enhanced behavioural support focusing on adherence to smoking cessation medications can improve adherence, and therefore recommends that interventions to increase adherence should address the practicalities and perception changes about taking medication. [191][192][193][194][195] As such, counselling interventions given outside routine clinical care by smoking cessation counsellors, including health educators and psychologists, could assist smokers to quit. 195 In respect to unwillingness to quit, in the UK about 40% of smokers do not want to quit, and despite the reduction in smoking rates across Europe since 2000, these rates are less pronounced compared to Australia and North America.…”
Section: Discussionmentioning
confidence: 99%
“…We created matched control and intervention condition protocols based on evidence-based tobacco cessation programs, including motivation and skill building, triggers, coping with cravings, coping with withdrawal, problem solving/relapse prevention, and the use of nicotine replacement therapy (NRT). 32 Each condition featured 6 sessions that covered the same topics in sequence. 32 However, the control condition used an approach guided by cognitive behavioral theory (CBT) and the intervention condition used a guided imagery approach, including personalized guided imagery scripts.…”
Section: Phase I: Integration Of Evidence-based Guided Imagery Practimentioning
confidence: 99%
“…32 Each condition featured 6 sessions that covered the same topics in sequence. 32 However, the control condition used an approach guided by cognitive behavioral theory (CBT) and the intervention condition used a guided imagery approach, including personalized guided imagery scripts. To create these scripts, trained coaches elicit sensory and emotion-rich information from participants related to quitting smoking, and work with participants to craft this information into a vivid guided imagery script which is recorded for repeated listening.…”
Section: Phase I: Integration Of Evidence-based Guided Imagery Practimentioning
confidence: 99%
“…The services routinely offered by quitlines for smoking cessation include telephone counselling (reactive and/or proactive) and written materials [1]. Telephone counselling is an accessible and flexible mode for delivering smoking cessation support [1][2][3] that has been shown to increase quitting success [4][5][6] and is cost effective [7]. The advantages of telephone services that assist people to quit include that: support can be tailored to individual needs; they are widely accessible; they eliminate the need to travel to access services; and they can reach rural and remote populations that may have limited access to in-person smoking cessation interventions [2].…”
Section: Introductionmentioning
confidence: 99%